Active Smoking May Negatively Affect Response Rate, Progression‐Free Survival, and Overall Survival of Patients With Metastatic Renal Cell Carcinoma Treated With Sunitinib. (5th December 2013) - Keizman, Daniel; Gottfried, Maya; Ish‐Shalom, Maya; Maimon, Natalie; Peer, Avivit; Neumann, Avivit; Hammers, Hans; Eisenberger, Mario A.; Sinibaldi, Victoria; Pili, Roberto; Hayat, Henry; Kovel, Svetlana; et al.
Learning Objectives: Describe the association between risk factors for renal cell carcinoma and the outcome of sunitinib treatment for metastatic disease. Explain the impact of active smoking on the outcome of sunitinib‐treated metastatic renal cell carcinoma. Discuss obesity, hypertension, and diabetes in relation to the outcome of sunitinib‐treated metastatic renal cell carcinoma. Abstract : Background: Obesity, smoking, hypertension, and diabetes are risk factors for renal cell carcinoma development. Their presence has been associated with a worse outcome in various cancers. We sought to determine their association with outcome of sunitinib treatment in metastatic renal cell carcinoma (mRCC). Methods: An international multicenter retrospective study of sunitinib‐treated mRCC patients was performed. Multivariate analyses were performed to determine the association between outcome and the pretreatment status of smoking, body mass index, hypertension, diabetes, and other known prognostic factors. Results: Between 2004 and 2013, 278 mRCC patients were treated with sunitinib: 59 were active smokers, 67 were obese, 73 were diabetic, and 165 had pretreatment hypertension. Median progression‐free survival (PFS) was 9 months, and overall survival (OS) was 22 months. Factors associated with PFS were smoking status (past and active smokers: hazard ratio [HR]: 1.17, p = .39; never smokers: HR: 2.94, p < .0001), non‐clear cell histology (HR: 1.62, p = .011), pretreatment neutrophil‐to‐lymphocyte ratio >3 (HR: 3.51, p < .0001), use of angiotensin system inhibitors (HR: 0.63, p = .01), sunitinib dose reduction or treatment interruption (HR: 0.72, p = .045), and Heng risk (good and intermediate risk: HR: 1.07, p = .77; poor risk: HR: 1.87, p = .046). Factors associated with OS were smoking status (past and active smokers: HR: 1.25, p = .29; never smokers: HR: 2.7, p < .0001), pretreatment neutrophil‐to‐lymphocyte ratio >3 (HR: 2.95, p < .0001), and sunitinib‐induced hypertension (HR: 0.57, p = .002). Conclusion: Active smoking may negatively affect the PFS and OS of sunitinib‐treated mRCC. Clinicians should consider advising patients to quit smoking at initiation of sunitinib treatment for mRCC. Abstract : An international multicenter retrospective study of sunitinib‐treated metastatic renal cell carcinoma patients was performed to determine the association between outcome and the pretreatment status of smoking, body mass index, hypertension, diabetes, and other known prognostic factors. The results showed that active smoking may negatively affect the progression‐free and overall survival of these patients. Abstract : 摘要 背景 。肥胖、吸烟、高血压以及糖尿病是肾细胞癌发展的风险因素。它们在各种癌症中都可导致疾病转归变差。本研究旨在明确以上状况在受舒尼替尼治疗的转移性肾细胞癌（mRCC）中与疾病转归的相关性。 方法 。在本次国际性、多中心、回顾性研究中，入组受舒尼替尼治疗的mRCC患者。通过多变量分析来明确吸烟、体重指数、高血压、糖尿病以及其他已知预后因素与疾病转归的关联。 结果 。2004∼2013年间，在接受舒尼替尼治疗的278例mRCC患者中：59例为主动吸烟者，67例肥胖，73例患有糖尿病，165例为预处理高血压。中位无疾病进展生存期（PFS）为9个月，总生存期（OS）为22个月。PFS相关因素包括吸烟状态（既往吸烟与现行主动吸烟者：风险比[HR]：1.17， p = 0.39；从不吸烟者：HR：2.94， p ˂ 0.0001），非透明细胞组织学类型（HR：1.62， p = 0.011），预处理中性粒细胞与淋巴细胞比例> 3（HR：3.51， p ˂ 0.0001），使用血管紧张素抑制剂（HR：0.63； p = 0.01），舒尼替尼供药量减少或治疗中断（HR：0.72； p = 0.045）以及Heng风险（低中风险：HR：1.07； p = 0.77；高风险：HR：1.87， p = 0.046）。OS相关因素包括吸烟状态（既往吸烟与现行主动吸烟者：HR：1.25； p = 0.29；从不吸烟者：HR：2.7， p ˂ 0.0001），预处理中性粒细胞与淋巴细胞比例> 3（HR：2.95； p ˂ 0.0001）以及舒尼替尼诱导的高血压（HR：0.57； p = 0.002）。 结论 。现行主动吸烟可能对接受舒尼替尼治疗的mRCC患者的PFS与OS产生不良影响。临床医生在开始对mRCC患者进行舒尼替尼治疗时，应建议其戒烟。 The Oncologist 2014;19:1‐10